2021
DOI: 10.1088/1742-6596/1882/1/012153
|View full text |Cite
|
Sign up to set email alerts
|

Improving ISLE-based STEM learning outcomes for building the 21st century skills and characters through a lesson study: A case study on Torque and Moment of Inertia

Abstract: The objectives of this study are as follows: (1) Developing ISLE-based STEM learning media, (2) Building 21st-century skills and character, (3) Analyzing the improvement of learning outcomes through lesson study. This research is a descriptive quantitative study developed at the STEM UNSYIAH Research Center and carried out at Unsyiah Laboratory High School. The instruments used in this study are validation rubric for media and material experts and Teacher Observation sheets and monitoring sheets for the increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…This is supported by the average value of the pretest-posttest which has increased by 0.75 with high criteria. In accordance with the research results of Ulfa, et al (2021) that ISLE-based learning is very suitable for improving 21st century skills including students' creative thinking skills.…”
Section: Figure 1 Comparison Of Pretest-posttest Scores Of Creativesupporting
confidence: 81%
See 1 more Smart Citation
“…This is supported by the average value of the pretest-posttest which has increased by 0.75 with high criteria. In accordance with the research results of Ulfa, et al (2021) that ISLE-based learning is very suitable for improving 21st century skills including students' creative thinking skills.…”
Section: Figure 1 Comparison Of Pretest-posttest Scores Of Creativesupporting
confidence: 81%
“…The investigations conducted in the ISLE approach are more about building knowledge . Research on the development of ISLE-based learning devices has also been conducted by Ulfa, et al (2021) who found that ISLE-based learning devices can improve students' critical thinking skills, as well as critical thinking skills with interconnected creative skills in producing an effective thinking to solve a problem (Mayarni &Yulianti, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Besides using learning styles, improving learning outcomes can also be done with several methods, media or other learning models, including using problem-solving learning models (Alqurashi, 2019), interactive-invention teaching strategies (Ukoh, 2022), and generative learning models with virtual lab. (Li et al, 2019), the Inquiry learning method (Razali et al, 2020), the community science technology approach (Mulyanti et al, 2021), including discovery learning-based SWS (Junina et al, 2020), ELSE-based STEM training (Ulfa et al, 2021), virtual Lab-based SWS. PhET simulation (Halim et al, 2021), and the NHT model (Rahayu & Cahyadi, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The varied teaching philosophies and techniques within non-STEM subjects further complicate the integration of Lesson Study. Recognizing and addressing these differences is vital to making Lesson Study a relevant and valuable professional development tool for non-STEM educators (Ulfa et al, 2021).…”
Section: Discussionmentioning
confidence: 99%